Studies on Synthesis of Some Novel Heterocyclic Azlactone Derivatives and Imidazolinone Derivatives and their Antimicrobial Activity - Rakesh N. Mistry; K. R. Desai (E-Journal of Chemistry)
p - Methyl benzoic acid on reaction with phosphorus pentachloride gives p - methyl benzoyl chloride derivative which on condensation with glycine gives p - methyl benzoyl glycine derivative. Now, this p - methyl benzoyl glycine derivative on condensation with various substituted aldehydes gives corresponding substituted 4 - [aryl methylidine] - 2 - [p - methyl phenyl] - oxazole - 5 - one derivatives [1(a-j)]. Further, these derivatives [1(a-j)] on condensation with 4 , 4’ - diamino diphenyl sulphone gives corresponding substituted imidazolinone - dibenzsulphone derivatives [2(a-j)], on condensation with 4 , 4’ - diamino diphenyl methane gives corresponding substituted imidazolinone - dibenzmethane derivatives [3(a-j)], on condensation with 4,4’- diamino benzanilide gives corresponding substituted imidazolinone - benzanilide derivatives [4(a-j)] and on condensation with 2 - amino pyridine gives corresponding substituted imidazolinone - pyridine derivatives [5(a-j)] respectively. Structure elucidation of synthesised compounds has been made on the basis of elemental analysis, I.R. spectral studies and 1H N.M.R. spectral studies. The antimicrobial activity of the synthesised compounds has been studied against the cultures “Staphylococcus aureus”, “Escherichia coli” and “Candela albicans”.